Effect of physical fitness on colorectal tumor development in patients with familial adenomatous polyposis. Issue 38 (September 2019) - Nakamura, Tomiyo; Ishikawa, Hideki; Sakai, Toshiyuki; Ayabe, Makoto; Wakabayashi, Keiji; Mutoh, Michihiro; Matsuura, Nariaki
Abstract : Abstract: Although accumulated epidemiological evidence indicates that a good physical fitness level may prevent the development of sporadic colorectal cancer (CRC), few studies have examined the effect of physical fitness level on familial adenomatous polyposis (FAP). This cross-sectional study aimed to examine the relationship between physical fitness and CRC development in patients with FAP. A total of 119 patients (54 male; 65 female) with FAP, aged 17 to 73 years, underwent a step test to induce exercise stress. Predicted maximal oxygen uptake (VO2 max) was calculated for each patient by using heart rate as an index of physical fitness. The association of VO2 max with the presence or absence of CRC and polyp diameter was examined. Patients with FAP were divided into 3 categories according to their VO2 max (high, medium, and low). The association between maximum polyp size and VO2 max among the patients with FAP without a history of colectomy was examined. The risk of CRC was significantly higher in the low VO2 max group than in the high VO2 max group (odds ratio = 4.07; 95% confidence interval, 1.02–16.26). The maximum polyp diameter was significantly negatively correlated with the VO2 max among the patients with FAP without a history of colectomy ( r = −.44, P = .01). In the multiple linear regression analysis, maximum polyp diameter was independently correlated with VO2 max. Our results suggest a preventive association between physical fitness and CRC development or colorectal adenoma growth exists in patients with FAP. Abstract : Supplemental Digital Content is available in the text